2016
DOI: 10.1007/s00421-016-3408-9
|View full text |Cite
|
Sign up to set email alerts
|

Pedelecs as a physically active transportation mode

Abstract: Participants rode a pedelec in the real world at a self-selected moderate intensity, which helped them meet physical activity recommendations. Pedelec commuting also resulted in significant improvements in 2-h post-OGTT glucose, [Formula: see text], and power output. Pedelecs are an effective form of active transportation that can improve some cardiometabolic risk factors within only 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 25 publications
10
54
0
3
Order By: Relevance
“…In addition, we found that heart rate during e‐cycling was within the range sufficient to increase cardiorespiratory fitness and was comparable to experimental studies in younger healthy individuals where e‐cycling elicited a heart rate of 67–69% HR max over a flat circuit 15 and 80–84% HR max on an uphill route 14. Increased fitness through e‐cycling may be predictive of improvements in cardiometabolic risk factors 19, with a recent study reporting improved response to an oral glucose tolerance test in healthy individuals 20, suggesting that e‐cycling may have potential for improving glucose control in people with Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, we found that heart rate during e‐cycling was within the range sufficient to increase cardiorespiratory fitness and was comparable to experimental studies in younger healthy individuals where e‐cycling elicited a heart rate of 67–69% HR max over a flat circuit 15 and 80–84% HR max on an uphill route 14. Increased fitness through e‐cycling may be predictive of improvements in cardiometabolic risk factors 19, with a recent study reporting improved response to an oral glucose tolerance test in healthy individuals 20, suggesting that e‐cycling may have potential for improving glucose control in people with Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, e-bike use in this study retained the majority of the cycling health benefit and met established biometric thresholds for cardiovascular fitness. The findings from the current study confirm two earlier findings from smaller studies in Europe, which also reported improvement in biometric outcomes relating to ebike usage [34,35].…”
Section: Principal Resultssupporting
confidence: 91%
“…Participants filled out the GPAQ in their preferred language. Moderate-intensity activities, vigorous-intensity activities, walking, cycling and e-bike trips were assigned a value for their metabolic equivalent of task (MET) of 4, 8 [26], 4, 6.8 [27] and 5 [28,29] respectively. Cleaning of GPAQ data and calculation of moderate to vigorous METminutes per week, minutes per day and sedentary minutes per day was performed according to the WHO GPAQ analysis guidelines [26].…”
Section: Methodsmentioning
confidence: 99%